Transgenic Gαq overexpression induces cardiac contractile failure in mice - D’Angelo, Drew D. (The National Academy of Sciences of the USA, 1997)
The critical cell signals that trigger cardiac hypertrophy and regulate the transition to heart failure are not known. To determine the role of Gαq-mediated signaling pathways in these events, transgenic mice were constructed that overexpressed wild-type Gαq in the heart using the α-myosin heavy chain promoter. Two-fold overexpression of Gαq showed no detectable effects, whereas 4-fold overexpression resulted in increased heart weight and myocyte size along with marked increases in atrial naturietic factor (≈55-fold), β-myosin heavy chain (≈8-fold), and α-skeletal actin (≈8-fold) expression, and decreased (≈3-fold) β-adrenergic receptor-stimulated adenylyl cyclase activity. All of these signals have been considered markers of hypertrophy or failure in other experimental systems or human heart failure. Echocardiography and in vivo cardiac hemodynamic studies indeed revealed impaired intrinsic contractility manifested as decreased fractional shortening (19 ± 2% vs. 41 ± 3%), dP/dt max, a negative force–frequency response, an altered Starling relationship, and blunted contractile responses to the β-adrenergic agonist dobutamine. At higher levels of Gαq overexpression, frank cardiac decompensation occurred in 3 of 6 animals with development of biventricular failure, pulmonary congestion, and death. The element within the pathway that appeared to be critical for these events was activation of protein kinase Cɛ. Interestingly, mitogen-activated protein kinase, which is postulated by some to be important in the hypertrophy program, was not activated. The Gαq overexpressor exhibits a biochemical and physiologic phenotype resembling both the compensated and decompensated phases of human cardiac hypertrophy and suggests a common mechanism for their pathogenesis.